ANTINOCICEPTIVE AND ANTIINFLAMMATORY EFFECTS OF ESSENTIAL OIL OF DENNETTIA TRIPETALA G.BAKER (ANNONACEAE) IN RODENTS - Oyemitan, I. A.; Iwalewa, E. O.; Akanmu, M. A.; Olugbade, T. A. (African Journal of Traditional, Complementary and Alternative Medicines, 2008)
In this study we evaluated the analgesic and anti- inflammatory activities of the essential oil (EO) of the fruits of Dennettia tripetala in rodents. The plant is a tropical African plant and the fruits are commonly eaten as spices and consumed as a stimulant, and its various parts are used in the treatment of fever, cough and as anti-emetics.The analgesic effects of the oil was assessed in mice using the hot plate, acetic acid-induced writhings and formalin test, while carrageenan-induced paw oedema was used to study the antiinflammatory effects in rats. The EO at 25-50 mg/kg exhibited significant (p<0.05) antinociceptive effects comparable to a potent opioid agonist, morphine (10 mg/kg) and non-steroidal anti-inflammatory drugs such as, aspirin (100 mg/kg) and indomethacin (80 mg/kg). The antinociceptive effect of the EO was also blocked by naloxone (2 mg/kg) in all the models used. The EO demonstrated significant (p<0.05) anti-inflammatory effect in the carrageenan-induced paw oedema model of inflammation that is also comparable to dexamethasone (1 mg/kg) The results showed that the essential oil of D.tripetala possesses significant antinociceptive and antiinflammatory effects in the animal models used. The results also suggest that the analgesic effects may be mediated both centrally as well as peripherally, while the antiinflammatory activity may be effective in both early and late phases of inflammation. The results obtained may therefore be used to rationalize the use of the plant in the treatment of pain and fever in traditional medicine.